The current status of online resources from the Portuguese Health System for childbirth education - Leite, Carla V. (2021)
In order to build knowledge and to make informed-decisions regarding childbirth, women need to gather information. Online resources can play a relevant role to its access, and health professionals can recommend, support and endorse it. The aim of this study is to understand the current state of e-health services for childbirth education provided by the Portuguese Health System. The data was collected from five portals: a) Portuguese National Patient Portal; b) Academia project website; c) Portuguese Health System website; d) Digital Library in Health Literacy; e) SNS24. Results show that childbirth topics are scarce or inexistent on those platforms. Only one document was found related to Pregnancy, with four pages regarding Childbirth, which were analysed according to the topics coverage, organisation, approach, and visual presentation. The results show that there is room for novel initiatives on e-health to promote childbirth education in Portugal.